Ectopic pregnancy with probable abdominal location treated with methotrexate: case report - Jakub Młodawski; Marta Młodawska; Joanna Baran; Grzegorz Świercz (Termedia Publishing House, 2023)
This paper presents the case of a 25-year-old patient who presented to the clinic with lower abdominal pain for several hours. On the basis of laboratory tests, history, and physical examination, a 5-week ectopic pregnancy was diagnosed, possibly located in the right fallopian tube. The patient was treated with a laparoscopic right salpingostomy. The immediate postoperative course was uneventful. The patient was discharged home with a recommendation to control the level of β human chorionic gonadotropin (β-hCG) in 7 days. After 2 weeks the patient returned to the clinic with symptoms of bleeding into the peritoneal cavity. A second laparoscopy with removal of the right fallopian tube and curettage of the uterine cavity were performed. Despite confirmation of the chorionic tissues by histopathology in the fallopian tube and the lack of confirmation of the chorionic tissues after the uterine cavity abrasion, the increased concentration of β--hCG and abdominal pain persisted after both procedures. Abdominal pregnancy was suspected, and a methotrexate single-dose therapy was initiated with satisfactory effect. The serum β--hCG concentration dropped by 29% after 4 days, and by 54% after 6 days, after 3 weeks the β--hCG level dropped to undetectable.